The size of others' burdens : Barack Obama, Jane Addams, and the politics of helping others - Schneiderhan, Erik (Professor of sociology) (Stanford University Press, 2015)
Americans have a fierce spirit of individualism. We pride ourselves on self-reliance, on bootstrapping our way to success. Yet, we also believe in helping those in need, and we turn to our neighbors in times of crisis. The tension between these competing values is evident, and how we balance between these competing values holds real consequences for community health and well-being. In his new book, The Size of Others' Burdens, Erik Schneiderhan asks how people can act in the face of competing pressures, and explores the stories of two famous Americans to develop present-day lessons for improvi.